PLAN DE DESARROLLO TERRITORIAL PARA LA PARROQUIA NAMBACOLA, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA, PERÍODO 2014-2019 - Jaramillo Hidalgo, Cristina Dolores (2018)
The Nambacola parish is an important sector for the economy of the canton Gonzanamá , however has had to go through various problems, such as situations of inequality, backwardness, government neglect , but above all, do not have an economic development plan and territorial obey to the real needs and expectations of the population, and which becomes an instrument to generate economic welfare among the population nambacolence. Besides , have not yet been research related matters, in the parish , which has generated a gap in knowledge. In this situation, conducted the research entitled " Spatial Development Plan for Nambacola Parish , Canton Gonzanamá , Province of Loja, period 2014-2019 ". Its overall objective was to develop a systematic and participatory assessment of the parish Nambacola Region Gonzanamá province of Loja, using the methodology of the National Secretary of Planning and Development ( SENPLADES ) , in order to formulate a plan of territorial development that improves the living standard of the population. In this research , the population consisted of 1,708 families. For methodological convenience, we worked with a representative sample of 314 families; having applied stratified sampling . The terms of the scientific method used was the inductive , deductive , analytic and synthetic. As techniques, followed literature and survey, and the formulation of territorial development plan of the SENPLADES. The main result of this investigation was that the parish